Noise reduction in the ICU: a best practice implementation project. Issue 4 (24th December 2022) - Souza, Regina Claudia da Silva; Calache, Ana Lucia Siqueira Costa; Oliveira, Ester Goes; Nascimento, Jonl Carlos do; Silva, Natalia Dalforno da; Poveda, Vanessa de Brito
ABSTRACT: Introduction: Sleep deprivation is a relevant problem among patients hospitalized in ICUs. Further, noise is the most critical disruptive factor according to patients. Objective: To implement scientific evidence-based best practices for noise control in an adult ICU. Methods: This was an evidence-based implementation project of best practices in noise control, conducted in a high-complexity hospital's adult ICU. The intervention consisted of three steps: baseline audit and identification of barriers, implementation of best practices, and a follow-up audit. Results: No compliance with best practices was detected in the baseline audit. After the implementation phase, the unit reached compliance levels of 78–88% for most of these criteria only one criterion related to noise level did not match the expected compliance. Conclusion: Adherence to best practices regarding noise control was satisfactory, achieving more than 70% compliance in the six audit criteria. Only the noise level did not reach the threshold recommended by the WHO - a difficulty reported in other studies. Relevance to clinical practice: Best practices related to noise control are essential for managing sleep deprivation in ICUs and include changes in the behaviour of involved professionals.